Konsep Dasar Penyusunan Hipotesis dan Kajian Teori dalam Penelitian - Hamdani, Hamdani; Sa’diyah, Halimatus (STAI Nurul Islam Mojokerto, 2025)
One of the mandatory tasks for students is to carry out research. Research can be said to be successful if the student understands every element in research subsections such as theoretical studies and hypotheses and is able to complete it in accordance with the regulations for scientific writing at each higher education institution where the student studies. The aim of this research is to find out the meaning, benefits and use of theoretical studies and hypotheses in research. The results of this research show that: 1) the definition of theoretical studies is a collection of theories or theoretical points taken from relevant sources in order to serve as the main reference for the phenomenon or problem being raised, while the definition of a hypothesis itself is an answer that is temporary in nature. needs to be tested for truth, 2) The benefit of theoretical studies can be a reference in developing research, can be a reference in determining criteria or as material for verifying research results, while the benefit of having a hypothesis is that it can provide direction in determining or interpreting data, can be a reference for procedures about what that must be done and collected and is useful in order to draw conclusions. 3) The steps for studying theory and hypotheses are the same, namely by reading a lot and studying research, only in determining the theoretical study it must be formulated with the problem/phenomenon being raised.